Commercially standardized process for probiotic "Italico" cheese production. (June 2017) - Blaiotta, Giuseppe; Murru, Nicoletta; Di Cerbo, Alessandro; Succi, Mariantonietta; Coppola, Raffaele; Aponte, Maria
Abstract: Modulation of the intestinal microbiota is one of the potential health-beneficial effects of probiotic foods. The market potential and the consumers' awareness about the impact of these foods on health, annually increases. Dairy industry seems to be a promising sector for new products' development. In the present study, the most suitable probiotic for "Italico" cheese production was assessed. Moreover, the ability as carrier for probiotics as well as the sensory quality of the Italico cheese was evaluated on both laboratory and industrial scale. Lactobacillus rhamnosus LbGG and SP1, within cheese samples, showed a remarkable tolerance to acid-gastric and duodenal stresses, up to 40 days of ripening at 4 °C, keeping a viability level higher than 10 8  CFU/g. Furthermore, the odor of the cheese enriched with these two probiotic strains appeared more acidic, creamy, buttery, and characterized by a pleasant matrix deconstruction, resulting in a Stracchino-like product. To authors' knowledge, this is the first study in which probiotic cheese production was followed at industrial level, thus fully describing an attractive system for commercial exploitation. Highlights: A standardized process to produce probiotic Italico cheese was described. Probiotic strains of L. rhamnosus within the Italico cheese showed a remarkable tolerance to gastro-intestinal stress. A daily serving dose of probiotic Italico cheese allows an intake of about 10 9 CFU of viable probiotic lactobacilli. Italico cheese produced with selected probiotic strains of L. rhamnosus showed improved sensory parameters.